Emergency surgical approach to incarcerated femoral hernias - ERSOY, Yeliz Emine; AYAN, Fadıl; Paksoy, Melih; AYDOĞAN, Fatih (Cerrahpaşa Medical Journal, 2014)
Today incarcerated inguinal hernia is one of the initial reasons that causes acute abdomen and requires surgery especially in old patients. Surgery after incarceration and strangulation increases the risk of morbidity and mortality. The aim of this study is to determine the factors that can affect the results of emergency femoral hernia repairs. Records of the 20 patients (22.2 %) who are dignosed hith femoral hernia among 90 patients with incarcerated inguinal hernia who presented to Istanbul University, Cerrahpasa Medical Faculty Emergency Department between years 2000-2004, were analyzed retrospectively. Mean age was 68.5 ± 15.87 years (38-86 years) in women and 58.5 ± 21.24 years (37-88 years) in men. 13 patients (65 %) were over the age of 60. Concomitant diseases were COLD (Chronic Obstructive Long Disease) in seven patients (35 %) and congestive heart failure in six (30 %). Moreover, two patients (10 %) had the history of myokardial infarction, four (20 %) had diyabetes and one (5 %) had small bowel tuberculosis. Seven patients (35 %) required small bowel resection and an end-to-end anastomosis was performed. Postoperatively, thre patients (13 %) had wound infection, two (10 %) had hematoma and one (5 %) had scrotal ecchymosis. Thre (15 %) patients were transformed to intensive care unit postoperatively because of cardiac and respiratory problems. All of the patients were discharged from the hospital after recovery. Results of this study showed that factors like advanced age, long lasting hernia symptoms, concomitant diseases had worsening effects suchas intestinal resection, langer of hospital stay. Early diagnosis and elective surgery are important factors in hernia treatment. If surgery is performed late, especially after incarceration and strangulation morbidity and mortality are significantly higher.